Pterostilbene Ameliorates Fumonisin B1-Induced Cytotoxic Effect by Interfering in the Activation of JAK/STAT Pathway - Jian Jin; Yiyi Shan; Liangliang Zhang; Zhengchang Wu; Shenglong Wu; Mingan Sun; Wenbin Bao (MDPI AG, 2022)
Fumonisin B1 (FB1) is a mycotoxin that poses a great threat to agricultural production and the health of humans and animals. Pterostilbene (PTE) is a natural plant polyphenolic compound with good anti-inflammatory, antioxidant and cell regeneration effects, yet its effectiveness in treating FB1-induced cytotoxicity remains to be explored. In this study, we used porcine alveolar macrophages (3D4/21) as a model to characterize the cytotoxicity induced by FB1, and to investigate the potential alleviating effect of PTE on FB1-induced cytotoxicity. We demonstrate that FB1 induces cytotoxicity, apoptosis, pro-inflammatory cytokine production and mitochondrial damage, which can be largely recovered by PTE treatment, suggesting the promising application of PTE to treat FB1-induced damage. Mechanistically, FB1 activates the JAK/STAT signaling pathway, while PTE attenuates FB1-induced cytotoxicity through the inhibition of key JAK/STAT genes such as JAK2 and STAT3. Overall, our study characterized the molecular mechanism for FB1-induced cytotoxicity and found PTE to be a promising component which can alleviate FB1-induced cytotoxicity by interfering in the activation of JAK/STAT pathway.